Hubungan Kecerdasan Emosional Terhadap Penyesuaian Diri Pada Pasien Kanker Serviks Paska Histerektomi - Robertus Surjoseto; Devy Sofyanty (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Emotional intelligence plays an important role in addressing various issues, especially self adjustment problems in post hysterectomy cervical cancer patients. This quantitative research with the correlational approach aims to determine the relationship between emotional intelligence and self adjustment in post hysterectomy cervical cancer patients. Sampling used is saturated sampling method which involve the entire population to be used as a research sample because the population was less than 100 people, namely 30 patient. To collect data using questionnaires and interview. The technique for the analysis used by the researcher in this study is Pearson’s product moment correlation. The analysis shows that there is a relationship between emotional intelligence and self adjustment. Emotional intelligence also had a direct and positive relationship with self adjustment, in which the value of r = 0,874; there is no negative sign, and it can be said that emotional intelligence and self adjustment have a very strong relationship.